Multiplicative methodology for assessing investment attractiveness and risk for industries - Yulia Vertakova; Maria Klevtsova; Anna Zadimidchenko (Journal of Risk and Financial Management, 2022)
Creating favorable conditions for the development of industry is one of the key tasks with an increased level of complexity, the solution of which is associated with attracting investments and forming an investment policy that takes into account various specific characteristics of its implementation. However, modern science requires a deeper development of tools related to the study of the investment attractiveness of industries and the level of risk of investing in them, including taking into account market value factors. The purpose of this study is the development and practical approbation of a multiplicative methodology for assessing investment attractiveness and risk for individual industries. The methodological basis of the study was the scientific works of domestic and foreign scientists in the field of industrial and investment policy, its goals, tools for implementation and features of formation in individual industry complexes. The work also used the methods of structural-functional, economic-statistical, and comparative analysis, as well as tabular and graphical interpretation of empirical-factual information. The proposed methods for assessing investment attractiveness make it possible to take into account not only quantitatively measured indicators, but also more obscure indicators, which is especially important for obtaining a more complete result and can be used in conditions of limited access to information. As a result of this study, the most investment-attractive enterprises and a separate industry were identified, which at the initial stage should become the priorities of the industrial policy of the regions, since they are a kind of growth pole that can create a propulsive effect for the development of other enterprises and the territory as a whole.
Keywords: G11; G14; G18; G21; G33; C00; 650; investment attractiveness; risks; industries; multiplicative methodology